An Outcome Study of a 2-Flap Pushback Palatoplasty Used in the Treatment of Wide Cleft Palates. Issue 3 (May 2015) - Lin, Kant Y.; Black, Jonathan S.; Wang, Jessica S.; Kerpelman, Jocelyn; Ho, Thuy-Van Tina; Borowitz, Kathleen
<x xml:space="preserve">Abstract</x> Abstract Cleft palate remains a common congenital deformity. The wide cleft palate in particular presents a unique challenge when attempting to restore a competent velopharyngeal mechanism. We present an outcome study of a single surgeon's experience using a modified surgical technique designed to specifically address the wide cleft palate. The surgical technique consisted of a 2-flap pushback palatoplasty without nasal mucosa closure combined with an end-to-end intravelar veloplasty and was used in cleft palates greater than or equal to 10 mm in width. A retrospective, longitudinal outcome study from chart review was then performed where age at surgery, sex, Veau classification of the cleft type, and follow-up length were recorded for each patient. Postsurgery speech outcomes were assessed by standardized speech evaluation performed by a speech language pathologist, and the presence and location of unplanned oronasal fistulas were recorded. Our study revealed an overall incidence of velopharyngeal insufficiency (VPI) of 10.8% and an unplanned symptomatic fistula rate of 16.8%. There was a significant correlation between the Veau classification of the cleft type with the incidence of both VPI and the occurrence of an unplanned oronasal fistula. Application of this surgical technique, specifically to wider cleft palates, resulted in VPI and fistula rates comparable to rates reported with other techniques used in clefts of all widths. Additional information regarding subsequent growth disturbances of the craniofacial skeleton in these patients is currently being collected.